KETAHANAN KAYU GERGAJIAN KOMERSIL DI KOTA AMBON TERHADAP SERANGAN RAYAP - Jimmy Titarsole; Rohny Setiawan Maail; Jimmy Johanson Fransz (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
This study was conducted to determine the resilience of sawn timber traded in the city of Ambon against the attack of wood destroyer organisms namely dry wood termite (Cryptotermes cynocephalus Light) and subteranian termite (Coptotermes curvignathus Holmgren). The results showed that from feeding 3 types of wood using 3 types of preservatives on dry wood termites, Meranti with preservatives 1 (LATREX 400 EC) has the highest level of dried wood termites (48%), while Pulai with Papaya Leaf extract has the lowest mortality rate of dry wood termites (24%). The average loss of wood weight due to dry wood termite attack ranged from 4.04 to 11.68%, where the preservatives of papaya leaf extract have the highest weight loss of 11.68%, the lowest (4.04%) on Meranti with preservatives 1 (LATREX 400 EC). The level of weight loss test sample wood feeders that have been given preservatives against soil termite attack are very different in real with the treatment of solid wood comparator (control) of each type, where the percentage of weight loss test sample of wood that uses preservatives between 11.04-18.71%, while the percentage of weight loss of solid wood Meranti, Samama, and Pulai (without preservatives) amounted to 36.39%, 46.04% and 58.65%. Commercial sawn timber in the city of Ambon is more resistant to the attack of dry wood and soil termites when given the treatment of wood preservatives.